Spatial distribution of prokaryotic symbionts and ammoxidation, denitrifier bacteria in marine sponge Astrosclera willeyana - Yang, Zhenya (Nature Publishing Group, 2012)
The present knowledge of microbial community mainly focus on total sponge, the spatial distribution of microbes in sponges is rarely known, especially those with potential ecological functions. In this study, based on gene library and ∫-LIBSHUFF analysis, the spatial distribution of prokaryotic symbionts and nitrogen cycling genes in the cortex and endosome sections of sponge Astrosclera willeyana were investigated. A significance difference of bacterial phylotypes between the cortex and endosome was revealed. For example Bacteroidetes, Frankineae and Propionibacterineae were detected only in the endosome, whereas Cyanobacteria, Planctomycetacia and Micrococcineae were only associated with the cortex. Some branches of α-Proteobacteria, γ-Proteobacteria, Corynebacterineae, Acidimicobidae, Crenarchaeota and Euryarchaeota also showed distribution difference. Bacterial denitrifiers and ammonia oxidizing bacteria (AOB) were observed using nirS and amoA genes as markers. Particularly, AOB were only associated with the endosome. This study highlighted the spatial distribution of bacterial symbionts especially those with ammonia oxidization function.